Synthesis In Silico and ADMET Profile of Triazinethione Derivatives for Their Potential as Anti-Inflammatory Agents - Ainaa Nadiah, Abd Halim; Nur Aina Syahira, Zikri; Zainab, Ngaini; Nor Hisam, Zamakshshari; Wei, Y. K.; D. Noissy, Diosing (Springer Nature, 2023)
A series of triazinethiones was successfully synthesized through cycloaddition reaction between guanidine hydrochloride with isothiocyanate intermediates and further analyzed through in silico analysis employing molecular docking simulations and ADMET prediction to investigate their potential anti-inflammatory activity. The ADMET profile of the synthesized triazinethione derivatives were found to possess favorable drug-like properties with good solubility (0.58–1.89 mg/mL) and oral bioavailability (0.55). The molecular docking analysis showed that among the synthesized triazinethione, 6-amino-4-(4-nitrophenyl)-1,3,5-triazine-2(1H)-thione exhibited a higher binding affinity with anti-inflammatory related enzymes, COX-2 (–7.8 kcal/mol) and iNOS (–6.1 kcal/mol) in comparison to standard drugs of salicylic acid (–6.2 kcal/mol) and Imidazopyridines (–5.9 kcal/mol), respectively owing to the hydrogen bond and hydrophobic interaction. The findings imply that triazinethione derivatives could make excellent possibilities for the development of new anti-inflammatory drugs